2018
DOI: 10.1038/s41467-018-07721-w
|View full text |Cite
|
Sign up to set email alerts
|

Closed-loop functional optogenetic stimulation

Abstract: Optogenetics has been used to orchestrate temporal- and tissue-specific control of neural tissues and offers a wealth of unique advantages for neuromuscular control. Here, we establish a closed-loop functional optogenetic stimulation (CL-FOS) system to control ankle joint position in murine models. Using the measurement of either joint angle or fascicle length as a feedback signal, we compare the controllability of CL-FOS to closed-loop functional electrical stimulation (CL-FES) and demonstrate significantly g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 37 publications
4
41
0
Order By: Relevance
“…recruitment occurs from fast-conducting fibres; Lertmanorat & Durand, 2004;Llewellyn et al 2010), DRG neurons with the best ChR2 transduction efficiency that should elicit the earliest and largest volley may not always be the fastest conducting neurons. A previous study reported that the recruitment order of afferent fibres by optical stimulation followed the expression levels of ChR2 (Srinivasan et al 2018). Therefore, we reasonably expected a slower conduction time in the optically elicited volley.…”
Section: Comparison Of Electrically and Optically Elicited Dorsal Roosupporting
confidence: 52%
See 4 more Smart Citations
“…recruitment occurs from fast-conducting fibres; Lertmanorat & Durand, 2004;Llewellyn et al 2010), DRG neurons with the best ChR2 transduction efficiency that should elicit the earliest and largest volley may not always be the fastest conducting neurons. A previous study reported that the recruitment order of afferent fibres by optical stimulation followed the expression levels of ChR2 (Srinivasan et al 2018). Therefore, we reasonably expected a slower conduction time in the optically elicited volley.…”
Section: Comparison Of Electrically and Optically Elicited Dorsal Roosupporting
confidence: 52%
“…A previous study reported that the recruitment order of afferent fibres by optical stimulation followed the expression levels of ChR2 (Srinivasan et al . ). Therefore, we reasonably expected a slower conduction time in the optically elicited volley.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations